2015
DOI: 10.1016/j.neuroscience.2015.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Task-dependent changes of corticospinal excitability during observation and motor imagery of balance tasks

Abstract: Non-physical balance training has demonstrated to be efficient to improve postural control in young people. However, little is known about the potential to increase corticospinal excitability by mental simulation in lower leg muscles. Mental simulation of isolated, voluntary contractions of limb muscles increase corticospinal excitability but more automated tasks like walking seem to have no or only minor effects on motor-evoked potentials (MEPs) evoked by transcranial magnetic stimulation (TMS). This may be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 54 publications
(75 reference statements)
6
51
0
1
Order By: Relevance
“…Brain activation patterns depend on the kind of mental simulation (i.e., AO + MI, MI and AO) and on the postural task (i.e., static vs. dynamic). In line with this, we found that corticospinal excitability was also modulated depending on the postural task and the kind of mental simulation performed by young subjects (Mouthon et al, 2015). To date, however, it is unknown whether the internal mental representation of balance tasks undergoes age-related changes.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Brain activation patterns depend on the kind of mental simulation (i.e., AO + MI, MI and AO) and on the postural task (i.e., static vs. dynamic). In line with this, we found that corticospinal excitability was also modulated depending on the postural task and the kind of mental simulation performed by young subjects (Mouthon et al, 2015). To date, however, it is unknown whether the internal mental representation of balance tasks undergoes age-related changes.…”
Section: Introductionsupporting
confidence: 67%
“…All participants gave written consent, in accordance with the Declaration of Helsinki, before participating in this study which was approved by the local ethics committee of the canton Fribourg (014-CER-FR). Their data was compared with the results of a group of healthy young adults (aged 27 ± 4.6, five females) from a previous study (Mouthon et al, 2015). …”
Section: Methodsmentioning
confidence: 98%
“…First, corticospinal excitability, measured through the amplitudes of motor evoked potentials, during both AO and MI of hand gestures is reliably higher than control conditions (e.g., Clark et al, 2004; Williams et al, 2012; see Naish et al, 2014; Grosprêtre et al, 2016 for reviews). Second, AO+MI produces significantly greater facilitation of corticospinal excitability compared to AO (Ohno et al, 2011; Wright et al, 2014, 2016) and, in some cases, MI as well (Sakamoto et al, 2009; Tsukazaki et al, 2012; Mouthon et al, 2015). These effects have been demonstrated across a variety of tasks, including simple and sequential finger movements (Wright et al, 2014, 2016), gross and fine motor tasks (Sakamoto et al, 2009; Ohno et al, 2011) and coordination tasks (Tsukazaki et al, 2012; Mouthon et al, 2015).…”
Section: The Effects Of Motor Imagery During Action Observation: Empimentioning
confidence: 99%
“…Several studies have filmed the AO component from a first-person visual perspective (e.g., Villiger et al, 2013; Wright et al, 2014, 2016), while other studies have filmed the action from a third-person visual perspective (e.g., Eaves et al, 2014, 2016; Mouthon et al, 2015; Taube et al, 2015). In some cases, participants are instructed to explicitly image from a first person perspective, while in other cases they are only told to imagine themselves performing the observed movement, which may result in participants adopting either a first- or third-person imagery perspective, depending on their imagery perspective preference.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…The more balance demanding tasks need considerable motor activity (16). Increased sensory motor activity demand in the more challenging balance tasks is not compensated with functional knee brace (9).…”
Section: Discussionmentioning
confidence: 99%